2013
DOI: 10.1002/chem.201300845
|View full text |Cite
|
Sign up to set email alerts
|

A Dioxane Template for Highly Selective Epoxy Alcohol Cyclizations

Abstract: Ladder polyether natural products are a class of natural products denoted by their high functional group density and large number of well-defined stereocenters. They comprise the toxic component of harmful algal blooms (HABs), having significant negative economic and environmental ramifications. However, their mode of action, namely blocking various cellular ion channels, also denotes their promise as potential anticancer agents. Understanding their potential mode of biosynthesis will not only help with develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…However, whereas the polyTHP product shown in Scheme 1C features a non-functionalized THP template, 13 required a scaffold bearing functional group handles. Based on our experience with a 1,3-dioxane template, 16 the dimethyl acetonide was chosen due to its similar conformational and electronic properties and ease of removal for further elaboration.…”
Section: Retrosynthetic Analysismentioning
confidence: 99%
“…However, whereas the polyTHP product shown in Scheme 1C features a non-functionalized THP template, 13 required a scaffold bearing functional group handles. Based on our experience with a 1,3-dioxane template, 16 the dimethyl acetonide was chosen due to its similar conformational and electronic properties and ease of removal for further elaboration.…”
Section: Retrosynthetic Analysismentioning
confidence: 99%
“…4 Additionally, Murai has demonstrated that a methoxymethyl group can direct endo -cyclization through Lewis acid chelation. 5 Templating 6 allows for highly-selective THP formation without the need for directing groups, and we have reported the use of a preformed THP 7 or 1,3 dioxane 8 in water-promoted cyclizations. This approach has enabled the synthesis of THPs bearing methyl substituents at the ring junctions 9 as well as marine ladder polyether fragments via polyepoxide cascades.…”
mentioning
confidence: 99%
“…Initial studies investigated the monocyclization of bicycle 9 , which was synthesized from known 1,3-diol 2 8 in 11 steps (Scheme 1). We hypothesized that the introduction of an electron-withdrawing hydroxyl group would favor endo -cyclization, as it would destabilize partial positive charge buildup at the exo -site during cyclization.…”
mentioning
confidence: 99%
See 2 more Smart Citations